Choline Kinase Emerges as a Promising Drug Target in Gram-Positive Bacteria - Zimmerman, Tahl; Lacal, Juan Carlos; Ibrahim, Salam A. (Frontiers in Microbiology, 2019)
Both nosocomial pathogens, such as Streptococcus pneumoniae and Haemophilus influenzae and food-borne pathogens, such as Bacillus cereus and Clostridium perfringens are known to be detrimental to human and animal health. The effectiveness of currently used treatments for these pathogens becomes limited as resistant strains emerge. Therefore, new methods for eliminating bacterial pathogens must be developed continuously. This includes establishing novel targets to which drug discovery efforts could be focused. A promising method for discovering new drug targets in prokaryotes is to take advantage of the information available regarding the enzymatic pathways that have been established as drug targets in eukaryotic systems and explore the analogous pathways found in bacterial systems. This is an efficient strategy because the same inhibitors developed at considerable expense to block these pathways in eukaryotic systems could also be employed in prokaryotes. Drugs that are used to prevent diseases involving eukaryotic cells could be repurposed as antibiotics and antimicrobials for the control of bacteria pathogens. This strategy could be pursued whenever the primary and tertiary structures of a target are are conserved between eukaryotic and prokaryotes. A possible novel target fitting these parameters is choline kinase (ChoK), whose active site sequences are conserved (Figure 1) and whose tertiary structure (Figure 2) is maintained. Here, we describe why ChoK is a putative drug target by describing its role in the growth and pathogenesis of Gram-positive bacteria S. pneumoniae and the Gram-negative bacteria H. influenzae. Using S. pneumoniae as a model, we also present promising preliminary information that repurposing of drugs known to inhibit the human isoform of ChoK (hChoK), is a promising strategy for blocking the growth of S. pneumoniae cells and inhibiting the activity of the S. pneumoniae isoform of ChoK (sChok), with downstream physiological effects on the cell wall.